IMPLEMENTATION OF FACTOR ANALYSIS IN THE OPTICAL MANIFACTURING: IMPLEMENTATION OF FACTOR ANALYSIS IN THE OPTICAL MANIFACTURING - Stoyanov, Stiliyan; Boyanov, Petar; Zhekov, Zhikvo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
A model of factor analysis is developed in the process of designing of complex optical systems. Factor analysis is indispensable in designing of photometric and spectrophotometric optical-electronic devices which consist of entrance-scanning system by space, lens with inner focusing, collimator objective which ensure the entering of a parallel bundle of rays over a dispersing diffraction grate over a wave length, a chamber lens and respectively, a sensor. These and similar optical systems require higher degree of elimination of chromatic aberration, etc. which ensures good quality of the optical system and of the obtained results.